2000
DOI: 10.1054/bjoc.2000.1167
|View full text |Cite
|
Sign up to set email alerts
|

True

Abstract: SummaryThe family history of cancer in children treated for a solid malignant tumour in the Paediatric Oncology Department at Institute Gustave-Roussy, has been investigated. In order to determine the role of germline p53 mutations in genetic predisposition to childhood cancer, germline p53 mutations were sought in individuals with at least one relative (first-or second-degree relative or first cousin) affected by any cancer before 46 years of age, or affected by multiple cancers. Screening for germline p53 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(75 citation statements)
references
References 17 publications
2
69
1
3
Order By: Relevance
“…Reports by Birch et al [11] and Frebourg et al [12] reported constitutional TP53 mutations in 6 of 12 and 7 of 15 LFS families respectively, giving a proportion for recognised constitutional mutations in these families of 50%. More recently Chompret et al [13] reported mutations in 8 out of 16 LFS families. Varley et al [14] extended the series of Birch et al [11] used comprehensive, automated methods to sequence exons 1-11 and included all splice junctions, the promotor and the 3 0 -untranslated region.…”
Section: Introductionmentioning
confidence: 99%
“…Reports by Birch et al [11] and Frebourg et al [12] reported constitutional TP53 mutations in 6 of 12 and 7 of 15 LFS families respectively, giving a proportion for recognised constitutional mutations in these families of 50%. More recently Chompret et al [13] reported mutations in 8 out of 16 LFS families. Varley et al [14] extended the series of Birch et al [11] used comprehensive, automated methods to sequence exons 1-11 and included all splice junctions, the promotor and the 3 0 -untranslated region.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of these de novo germline mutations emphasizes the importance of TP53 mutation analysis in young patients with multiple malignancies that are part of the LFS spectrum or adrenocortical carcinoma irrespective of cancer history in their relatives, as suggested by the Chompret LFL criteria [7] but not by the classical LFS or other LFL criteria [5,6]. The second proband with adrenocortical carcinoma was a child of Brazilian origin presenting the p.Arg337His TP53 mutation (Table 1) previously reported as a founder mutation in southern Brazil [31][32][33] and in a single patient of Portuguese background living in France [16]. Since the proband's mother was a healthy carrier, the p.Arg337His mutation did not arise de novo and indeed it has been considered a low penetrance mutation that contributes in a tissue-specific manner to the development of adrenocortical carcinoma in childhood [34,35].…”
Section: Resultsmentioning
confidence: 94%
“…These data made possible the shift from clinical and familial criteria to genetic criteria for the definition of LFS. A significant proportion of the TP53 germline mutations occur de novo [14][15][16][17] and this contributes to the higher sensitivity of the Chompret LFL criteria to identify patients who are TP53 mutation carriers, as they allow inclusion of patients with multiple narrow spectrum LFS malignancies or with adrenocortical carcinomas irrespective of their family history of cancer [7,13].…”
Section: Introductionmentioning
confidence: 99%
“…In 1990, both Malkin et al[ 3] and Srivastava et al[ 26] found associations between germline TP53 mutations and families with LFS. Numerous studies have found a similar association, although germline TP53 mutations are only found in approximately 70% of classic LFS cases with an even lower incidence in LFL or families with a history of primary LFS spectrum tumors [1, 7, 10,27,28,29,30,31]. …”
Section: Discussionmentioning
confidence: 90%
“…Since their 3 cases, there have been 17 additional cases, including this report, of primary CPC, occurring in patients with LFS/LFL, germline TP53 mutations, or both [12, 13, 15, 29,45,46,47,48,49,50]. The number of such cases may be underestimated since many reports do not distinguish between types of CNS tumors or divide CPTs into papillomas and carcinomas [1,2,3,4,5, 23, 25, 26, 51, 52].…”
Section: Discussionmentioning
confidence: 99%